Etika Komunikasi Perangkat dalam Upaya Meningkatkan Pelayanan Masyarakat Desa Tepian Batang - Aisyah, Siti; Nurliah, Nurliah (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This study aims to describe the communication ethics of the Tepian Batang village apparatus in efforts to improve public services, as well as to identify and analyze the supporting and inhibiting factors of these communication ethics. The research was conducted at the Tepian Batang Village Office, Tanah Grogot Subdistrict, Paser Regency, East Kalimantan, from March to April 2025. Data analysis employed the interactive model by Miles and Huberman (2016). The results indicate that the communication ethics practiced by the village apparatus in enhancing public services are carried out through effective communication aspects and strong collaboration between the village head and village officials in socializing programs down to the neighborhood (RT) level, community groups (POKMAS), and PKK activists who are the policy targets. The village human resources effectively perform their duties through intensive coordination with POKMAS, RT, and PKK, as well as by compiling reports from community deliberations. he village budget, sourced from Village Funds (State Budget - APBN) and Village Allocation Funds (Regional Budget - APBD), with an allocation of approximately IDR 124.5 billion for Paser Regency in 2025, supports program implementation. The disposition of Tanah Grogot Subdistrict shows a strong commitment to the work programs, demonstrated by the subdistrict head’s direct involvement in socialization and the active role of POKMAS in overseeing community meetings and reporting the results to the village head. A bureaucratic structure at the subdistrict level functions to collect, verify, and coordinate village activity proposals and report implementation results to the regent.